The heiress at sea - Caldwell, Christi (Montlake, 2023)
"Perpetually unattached Lady Cassia McQuoid has accepted her fate as a spinster. But how can she be expected to lead a life confined to drawing rooms and royal balls when there's a vast, exciting world to explore? Cassia can find but one solution: she masquerades as a thrill-seeking lad and stows away on a ship bound for open waters. Adventure awaits. So does notorious privateer Nathaniel Ellsby"--